2022
DOI: 10.21203/rs.3.rs-1615826/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The SHDRA syndrome associated gene TMEM260 encodes a protein-specific O-mannosyltransferase

Abstract: Mutations in the TMEM260 gene cause structural heart defects and renal anomalies syndrome (SHDRA), but the function of the encoded protein remains unknown. We report that TMEM260 is an ER-located protein O-mannosyltransferase that selectively glycosylates defined extracellular immunoglobulin, plexin, transcription factor (IPT) domains of the hepatocyte growth factor receptor (cMET), macrophage-stimulating protein receptor (RON), and plexin receptors. We demonstrate that disease-causing TMEM260 mutations impair… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(52 citation statements)
references
References 0 publications
5
22
0
Order By: Relevance
“…3E ). Taken together, these results, which agree with previous studies (13,17,18), validated the approach and showed that our O-Man deconstruction cell library is suitable for analyses of pathway-specific substrate specificities.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…3E ). Taken together, these results, which agree with previous studies (13,17,18), validated the approach and showed that our O-Man deconstruction cell library is suitable for analyses of pathway-specific substrate specificities.…”
Section: Resultssupporting
confidence: 91%
“…2C ). As recently described, IPT domains are TMEM260 substrates (18), and here, we identified 7 members (PLXNA1-4, PLXNB2-3, PLXND1) of the plexin family, as well as cMET and RON receptors, which account to 9 proteins (of n=12 predicted) with O-Man on IPT domains. Interestingly, we also identified 26 proteins with O-Man on distinct Ig-like domains, including Ig-like C2-type domains (n=5), Fibronectin type-III domains (n=4) and Ig-like V-type domains (n=2), indicating that O-Man glycosyltransferases selectivity is not limited to the Ig-like fold subclasses defined by EC- and IPT-domains.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations